Reality Therapy untuk meningkatkan penyesuaian diri remaja dengan gangguan major depressive disorder - Intan Novantin Citra Ady (Procedia : Studi Kasus dan Intervensi Psikologi, 2021)
The subject is an 18-year-old prisoner who was diagnosed with Major Depressive Disorder. The assessments used include interviews, observations, WARTEGG tests, SSCT tests, and Graphic tests. The results of the assessment show that the subject is a person who is difﬁcult to adjust to a new environment, cannot accept his current life and wants to commit suicide. The intervention given was Reality Therapy which consisted of seven sessions. The purpose of this intervention is to help the subject to realize his own needs and make the right decisions for him. The results of the intervention showed that the subject became more accepting of his life in prison and could more calmly carry out activities in prison.